123 GAMMA-TOCOPHEROL INDUCES CELL DEATH AND APOPTOSIS IN HUMAN LEUKEMIA CELLS, KG-1. Issue 1 (1st January 2007) - Hammad, A.; Ho, C. X.; Salman, H.; Campbell, S.
Abstract : There is great country-to-country variation in the worldwide incidence of cancer. This suggests that diet may play an important role in the carcinogenesis process. Diets such as the Mediterranean diet, rich in antioxidants, including vitamin E, have protective effects against malignancies. Vitamin E is represented by eight structurally related compounds called "isoforms." Vitamin E-rich diets may help neutralize free radicals in tissues and prevent DNA damage. However, there is increasing evidence that vitamin E has regulatory effects that are independent of its antioxidant activity. E2A-Pbx1 chimeric oncoprotein results from fusion of the E2A and Pbx1 genes. Experimentally, E2A-Pbx1 transforms a variety of cell types, including myeloid progenitors, resulting in myeloid leukemia that are dependent on cytokines for survival but show impaired terminal differentiation. The objective of this study was to determine if vitamin E could induce cell death and apoptosis in KG-1 leukemia cells. We were also interested in determining if the E2A-Pbx-1 fusion protein expression could be down-regulated in the KG-1 leukemia cells by vitamin E treatment. KG-1 cells were treated with various concentrations of vitamin E. Cell death was measured by MTT assay. Apoptosis was measured by induction of caspase 3 by Western blot analysis. The down-regulation of E2A-Pbx-1 was measured by Western blot analysis. We discovered that vitamin E isoforms induce cell death and apoptosis in KG-1 leukemia cells by caspase 3 cleavage. In addition, we found that gamma-tocopherol down-regulates the E2a-Pbx1 fusion protein in KG-1 leukemia cells. This action may help induce cell differentiation and cell death. These data show that vitamin E isoforms might have a role to modulate leukemia cell death through various mechanisms.